2020
DOI: 10.3390/cancers12123759
|View full text |Cite
|
Sign up to set email alerts
|

HNC0014, a Multi-Targeted Small-Molecule, Inhibits Head and Neck Squamous Cell Carcinoma by Suppressing c-Met/STAT3/CD44/PD-L1 Oncoimmune Signature and Eliciting Antitumor Immune Responses

Abstract: Despite advancements in diagnostic and standard treatment modalities, including surgery, radiotherapy, and chemotherapy, overall survival rates of advanced-stage head and neck squamous cell carcinoma (HNSCC) patients have remained stagnant for over three decades. Failure of these treatment modalities, coupled with post-therapy complications, underscores the need for alternative interventions and an in-depth understanding of the complex signaling networks involved in developing treatment resistance. Using bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Hence, the identification of novel small molecules, which can regulate the overexpression of these genes, becomes crucial. We have earlier reported NSC777201 for some biological activities [ 25 , 26 , 67 ], herein, we used a molecular docking approach and an NCI’s ovarian cancer cell lines to evaluate its anti-cancer activity and explore its possibility for targeting TTK, NEK2, and CDK1. Interestingly, we found that NSC777201 exhibited anti-proliferative and dose-dependent cytotoxic activity against the NCI’s ovarian cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the identification of novel small molecules, which can regulate the overexpression of these genes, becomes crucial. We have earlier reported NSC777201 for some biological activities [ 25 , 26 , 67 ], herein, we used a molecular docking approach and an NCI’s ovarian cancer cell lines to evaluate its anti-cancer activity and explore its possibility for targeting TTK, NEK2, and CDK1. Interestingly, we found that NSC777201 exhibited anti-proliferative and dose-dependent cytotoxic activity against the NCI’s ovarian cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of water molecules, the addition of hydrogen atoms, and Kolmman charges in the receptor were made as prerequisites of pre-docking. Molecular docking studies were conducted using AutoDock VINA software and by following protocols described in our previous studies [ 67 , 83 , 84 , 85 ]. The best poses of ligand-receptor complexes of hydrogen bonds and electrostatic and hydrophobic interactions were expressed as binding energy values (kcal/mol) to represent docking results.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-docking preparation of the receptors followed the removal of water molecules, while hydrogen atoms and Kolmman charges were added accordingly. Molecular docking studies were performed using Autodock VINA software and by following the protocols described in our previous study [3]. The docking results based on hydrogen bonds and electrostatic and hydrophobic interactions of the best pose of the ligand-receptor complexes were expressed as binding energy values (kcal/mol).…”
Section: In Silico Molecular Docking Analysesmentioning
confidence: 99%
“…Despite advances in biomedical research, cancer remains a public health concern and is currently ranked the second leading cause of global mortality [1,2]. The etiology of cancer is often multifactorial, involving an interplay between genetic and epigenetic factors which amount to dysregulation of molecular networks, proteins, RNA, and DNA in favor of cell growth and proliferation [3,4]. The survival, growth, and metastasis of tumor cells depend on cellular differentiation, proliferation, angiogenic, and apoptotic mechanisms [5], which are controlled by a range of protein kinases and signal transduction pathways [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The ligands were prepared for docking by deletion of H 2 O molecules, adjustment of polar hydrogen, and addition of Kollman charges. The molecular docking was performed using AutoDock Vina with all parameters set as default, and all bonds in the ligand are rotated freely, considering the receptor as rigid [57][58][59]. A grid box of 40 Å × 40 Å × 40 Å was generated on defined binding site residues of the ligand.…”
Section: Histopathological Evaluation Of Testismentioning
confidence: 99%